Hubungan Social Support Dengan Academic Resilience Dimediasi Self - Regulated Learning Pada Mahasiswa Keperawatan Dimasa Pandemi Covid-19 - Betty Erda Yoelianita; Iswinarti; M. Salis Yuniardi (PROFESSIONAL HEALTH JOURNAL, 2023)
Introduction : The Covid-19 pandemic had affected of higher education, especially Nursing students in online clinical practice learning. The impact of online learning was students difficulties and limitations in direct clinical learning. A significant decrease in the statistical value of nursing practice pre-pandemic and during the pandemic. Academic resilience is very important and needed by students to overcome academic challenges difficulties and demands during a pandemic. Academic resilience shows students capacity to overcome difficulties related to education and learning through adaptive responses by using self-regulated learning (SRL). This study aims to examine the role of SRL as a mediator between social support and academic resilience for undergraduate nursing students during the Covid-19 pandemic. Methods : This study uses a quantitative approach, with a cross-sectional research design. The research sample consisted of 244 Bachelor of Nursing students PTN/PTS, taken using a purposive sampling technique. The inclusion criteria are Bachelor of Nursing students academic year 2018-2021 who have carried out clinical practice in hospitals and other practice areas, during the Covid-19 pandemic. The measuring instrument used are the MSPSS scale, the ARS-30 scale, and the SRL scale. Data analysis used Process Hayes Version 4.0 regression analysis with the IBM SPSS version 25 for windows program. Results: Statistical test results show a positive and significant relationship between social support and academic resilience directly (β=0.9920; p=0.000) or partially mediated by SRL (β=0.4640; p=0.000, LLCCI=0.2625 ;ULCI=0.6655). Conclusion : The important influence of social support on academic resilience occurs directly or indirectly mediated by SRL. The higher the social support, the higher the SRL which ultimately increases academic resilience.